MPLEMENTASI SLIP GAJI ELEKTRONIK DALAM RANGKA MENJANGKAU LOKASI KARYAWAN YANG BERTUGAS DI BERBAGAI LOKASI - Poetryono, Djati; Broto, Satrio (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2015)
Pay slips provided by the company to employees as a sign written evidence that the company has been paying the salaries of employees according to applicable regulations. In paychecks There are two areas, namely the area of income and area of the deduction. The difference between the two in the form of salary to be net received by employees. If company has a lot of work location, distribution of slip salaries in a timely manner to all employees to be something important. Delays in the receipt paychecks by employees in the field location can cause problems for the company. By utilizing information technology,such potenstial problem could be reduced significantly.